Les Principes De Jogjakarta: Principes sur l'application de la législation internationale des droits humains en matière dórientation sexuelle et d'identité de genre (2006)
Principes additionnels et obligations additionnelles des états au sujet de l’application du droit international des droits humains en matière d’orientation sexuelle, d’identité de genre, d’expression de genre et de caractéristiques sexuelles pour completer les Principes de Jogjakarta Depuis leur adoption en 2006, les Principes de Jogjakarta ont évolué pour devenir une déclaration faisant autorité sur les droits humains des personnes « d’orientations sexuelles et d’identités de genre diverses ». La dernière décennie a été témoin de développements significatifs dans le domaine du droit international des droits humains, ainsi que dans la compréhension des violations des droits humains subies par les personnes « d’orientations sexuelles et d’identités de genre diverses », et dans la reconnaissance des violations souvent distinctes touchant des personnes en raison de leur « expression de genre » ou de leurs « caractéristiques sexuelles ».Les Principes de Jogjakarta plus 10 (PJ+10) visent à documenter et à détailler ces développements à travers un ensemble de Principes additionnels et d’Obligations additionnelles des États.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; antiracisme; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; outils; pol4022; premier cycle; périodes historiques; queer; racisme; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Les conceptions de l’identité sexuelle, le postmodernisme et les textes littéraires - Boisclair, Isabelle; Saint-Martin, Lori (Recherches féministes, 2006)
Le présent article trace d’abord un bref portrait de trois conceptions dominantes de l’identité sexuelle : le modèle patriarcal, le modèle féministe et le modèle postmoderne. Puis, après avoir présenté plus longuement le dernier, il analyse deux romans relayant cette conception postmoderne de l’identité de sexe/genre, l’un écrit par un homme (Self, de Yann Martel, paru en 1996), et l’autre par une femme (Ce qu’il en reste, de Julie Hivon, paru en 1999). Dans ces deux romans, qui revêtent de ce fait une importante dimension politique, les identités figées sont mises à mal tant discursivement que formellement - par la déconstruction des signes du passé et la mise en place de dispositifs énonciatifs confondant hommes et femmes, par exemple. Ils participent ainsi à une conception culturaliste de l’identité sexuelle, selon laquelle le genre est une performance.,This article begins by briefly introducing three major frameworks for conceptualizing gender identity : a patriarchal model, a feminist model and a postmodern model. After exploring the third in greater depth, it offers a reading of two novels of postmodern gender identity, one by a male author (Self by Yann Martel, 1996), one by a female author (Ce qu’il en reste by Julie Hivon, 1999). Both novels, which are therefore strongly political, challenge the concept of predetermined gender identity on the levels both of discourse and of form, by deconstructing older concepts and by blurring gender lines. They are therefore grounded in a view of gender identity as cultural construction and performance.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; fem1000; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; études littéraires

Queer zones: politique des identités sexuelles et des savoirs - Bourcier, Marie-Hélène (Amsterdam, 2006)
Publié pour la première fois en 2001, ce livre pionnier a permis l'ouverture d'un espace théorique et politique queer en France. Il s'agit d'une boîte à outils destinée aux activistes en quête de cultures et de politiques sexuelles qui ne soient pas (homo ou hétéro) normatives. Stimulants et provocants, les textes réunis dans ce recueil constituent également une introduction critique à la déconstruction des genres et aux travaux de Judith Butler et de Michel Foucault. Ils mettent de plus en évidence l'apport des subcultures trans, butch et SM à une réflexion plus large sur les relations entre pouvoir et savoir, ainsi que le formidable potentiel des sexualités dissidentes et la continuité politique entre féminisme pro-sexe et activisme queer. Cette nouvelle édition comprend trois essais inédits sur le " devenir femme " de Deleuze, l'utopie sexuelle urbaine de Gayle Rubin et la post-pornographie selon Annie Sprinkle.
Keywords: approches et analyses; cours; discipline; fem1000; har4600; histoire; identités LGBTQIA2+; lit3220; militance; personnes trans*; politique; premier cycle; queer; sciences humaines; sexualité; thématiques; violences

Comment devient-on homo ou hétéro? - Clerget, Stéphane (JC Lattès, 2006)
Le pédopsychiatre présente les découvertes récentes de la psychanalyse, la neurobiologie, la génétique, l'histoire, la sociologie, etc., à propos de la construction de l'identité sexuelle et de la part d'inné et d'acquis dans la définition des préférences sexuelles.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Queering the Binaries: Transsituated Identities, Bodies, and Sexualities - Cromwell, Jason (The transgender studies reader, 2006)
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques; états-unis

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Routledge international encyclopedia of queer culture - Gerstner, David A. (Routledge, 2006)
The Routledge International Encyclopedia of Queer Culture covers gay, lesbian, bisexual, transgender and queer (GLBTQ) life and culture post-1945, with a strong international approach to the subject.The scope of the work is extremely comprehensive, with entries falling into the broad categories of Dance, Education, Film, Health, Homophobia, the Internet, Literature, Music, Performance, and Politics. Slang is also covered. The international contributors come from a wide array of backgrounds: scholars, journalists, artists, doctors, scientists, lawyers, activists, and an enormous range of ideologies and points of view are represented. Major entries provide in-depth information and consider the intellectual and cultural implications of their subjects in a global context. Information is completely up-to-date, including full coverage and analysis of such current or ongoing issues as same-sex marriage/civil union and the international AIDS epidemic. Additionally, there are important appendices covering international sodomy laws and archival institutions, which will be of great value to researchers. The Encyclopedia is fully cross-referenced and many entries carry a bibliography. Where possible internet references have been given and there is a full index.The combination of its wide scope, determined international coverage and appendices make the Routledge International Encyclopedia of Queer Culture a uniquely ambitious work and an extremely rich source of information. It is a priority addition for all libraries serving scholars and students with an interest in GLBTQ culture, history and politics across the disciplines.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; incontournable; outils; ouvrages de références; queer; ressource en ligne; thématiques

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Nous, enfants d'homos homoparentalité: une génération témoigne - Kaim, Stéphanie (Éd. de La Martinière, 2006)
A partir d'une enquête menée en France et en Californie, l'auteure décrit les conditions d'accession à l'homoparentalité, depuis le milieu des années 1970. Elle donne la parole à de jeunes adultes élevés par des homosexuels pour mieux poser la question de l'éducation et de l'orientation sexuelle de ces enfants.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; californie; cours; discipline; europe; filiation; france; identités LGBTQIA2+; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; shm4000; thématiques; états-unis

Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (Cultural front, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

La loi du genre : une histoire culturelle du troisième sexe - Murat, Laure (Histoire de la pensée, 2006)
Homme ou femme. Existe-t-il un espace viable entre ou hors ces deux catégories ? Une invention théorique et poétique a tenté de fournir, au cours de l'histoire, une réponse à cette question : le " troisième sexe ", celui qui défierait la loi du genre. L'expression désigne, à partir du XIXe siècle, les figures considérées comme déplacées par rapport aux canons de la virilité et de la féminité : les " tantinettes " traquées par la police dans le Paris de Balzac, les saphistes de roman et les invertis étudiés par la psychiatrie, les " fastueux travestis " des bals populaires, les femmes émancipées de la Belle Epoque et les premiers transsexuels opérés des années 1930. Derrière toutes ces figures dissidentes, l'idée d'un " troisième sexe " provoque, dérange et renvoie la société à cette énigme inépuisable : que signifie vraiment être une " femme " ou un " homme " ? Exploitant des archives inédites de la police, des textes méconnus de la sexologie ou de la littérature, Laure Murat a élaboré ici une analyse inattendue et passionnante, éclairant d'un jour nouveau l'archéologie des discours sur les questions de genre que notre époque ne cesse d'interroger.
Keywords: 1800-1899; 1900-1999; LGBTQIA2+; analyse de discours; approches et analyses; belle époque; cours; discipline; discours dominant; europe; fem1000; france; genre; his4860; histoire; homophobie; identités LGBTQIA2+; paris; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques; transphobie; troisième sexe

A bakhtinian perspective on feminist lesbian crime writing - Posman, Sarah (CLCWeb: Comparative Literature and Culture, 2006)
In her paper, "A Bakhtinian Perspective on Feminist Lesbian Crime Writing," Sarah Posman discusses how the Bakhtinian concepts "ethos" and "chronotope" add to the discussion of feminist lesbian crime writing. She sets out from a Bakhtinian typology of action stories and situates recent crime writing as a curious mixture of mission stories and transformation stories. Focusing on the innovative potential of feminist lesbian crime writing, Posman explores how such stories tackle the iconically masculine and heterosexual conventions of the detective story and manage to balance tradition and subversion successfully. Posman infuses her analysis with issues central to feminism and queer theory and considers how a feminist lesbian detective hero can "change the world," that is, how such an "other" ethos impinges on crime writing's conventional chronotopical constellation. The hero and world under discussion are those of the popular Kate Delafield series by Katherine V. Forrest.
Keywords: approches et analyses; arts; discipline; lesbianisme; personnes lesbiennes; queer; ressource en ligne; études littéraires

The transgender studies reader - Stryker, Susan; Whittle, Stephen (Routledge, 2006)
Although the term "transgender" itself has achieved familiarity only within the past decade, this authoritative collection of articles demonstrates that the study of behaviors, bodies, and subjective identities which contest common Eurocentric notions of gender has a history stretching back at least to the early 20th century. Transgender studies is the latest area of academic inquiry to grow out of the exciting nexus of queer theory, feminist studies, and the history of sexuality. Because transpeople challenge our most fundamental assumptions about the relationship between bodies, desire, and identity, the field is both fascinating and contentious. The Transgender Studies Reader puts between two covers fifty influential texts with new introductions by the editors that, taken together, document the evolution of transgender studies in the English-speaking world. By bringing together the voices and experience of transgender individuals, doctors, psychologists, and academically-based theorists, this volume will be a foundational text for the transgender community, transgender studies, and related queer theory.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; interdisciplinarité; occident; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis